2018
DOI: 10.2478/ejes-2018-0011
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Carbon Tax Application on the Economy and Environment of Indonesia

Abstract: As the most efficient market with a mitigation instrument basis, carbon tax is highly recommended by economists and international organizations. This paper examines the impact of implementing carbon tax policy on value of change in GDP, GDP Quantity Index, Government Household Demand, Private Household Demand, and CO2emission effects in Indonesia by using the dynamic energy Computable General Equilibrium (CGE) model. This study used GTAP-E that was part of GTAP 9 in 2011. GTAP-E consists of 140 countries and 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
0
3
0
1
Order By: Relevance
“…Puttanapong et al (2015) also found that increasing the carbon tax was able to reduce carbon emissions. Not only with the Dynamic CGE model, research using GTAP E (Nong, 2018 andAyu, 2018), the SAM model (Frey, 2017;Grottera et al, 2017), the MIT EPPA model (Octaviano et al, 2014) revealed that a carbon tax would be able to reduce carbon emissions.…”
Section: Impact Of Carbon Tax On the Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Puttanapong et al (2015) also found that increasing the carbon tax was able to reduce carbon emissions. Not only with the Dynamic CGE model, research using GTAP E (Nong, 2018 andAyu, 2018), the SAM model (Frey, 2017;Grottera et al, 2017), the MIT EPPA model (Octaviano et al, 2014) revealed that a carbon tax would be able to reduce carbon emissions.…”
Section: Impact Of Carbon Tax On the Environmentmentioning
confidence: 99%
“…This result is in line with Wattanakuljarus (2019) who also used the Dynamic computable general equilibrium (CGE) Model in Thailand, the use of a carbon tax of 20% was able to reduce emissions by 2030. Not only with the Dynamic CGE model, research using Global Trade Analysis Project (GTAP) E (Ayu, 2018;Bi et al, 2019;Cao et al, 2016;Coxhead et al, 2013;Kat et al, 2018;Nong, 2018;Nurdianto & Resosudarmo, 2016;Ojha et al, 2020;Ward & Batista, 2016;Yusuf & Resosudarmo, 2015), the SAM model (Frey, 2017;Grottera et al, 2017), the MIT EPPA model (Octaviano et al, 2014) reveals that a carbon tax will be able to reduce carbon emissions.…”
Section: Introductionmentioning
confidence: 99%
“…Model CGE yang umumnya digunakan untuk mengetahui dampak atas kebijakan energi adalah model CGE-IndoCEEM (Indonesia Clean Energy and Energy Conservation) yang dikembangkan oleh tim kolaborasi peneliti Batlibang ESDM (Badan Penelitian dan Pengembangan Energi dan Sumber Daya Mineral), Badan Kebijakan Fiskal Kementerian Keuangan, dan Monash University. Salah satu hasil pemodelan CGE memperlihatkan bahwa penerapan carbon tax di Indonesia efektif dapat mengurangi emisi karbon sebesar 9,6% jika ditetapkan tarif carbon tax sebesar 20 USD/tCO2e (Ayu, 2018). Penerapan carbon tax dapat menjadi sumber pendapatan besar pada industri-industri padat energi dan karbon seperti industri konstruksi, pulp dan kertas, tekstil, petrokimia, dan transportasi (Irama, 2019;Yusuf dan Resosudarmo, 2015).…”
Section: Penerapan Carbon Tax DI Indonesiaunclassified
“…Having such importance, only a few studies examine the impact of the carbon tax policy in Indonesia. A carbon tax policy is predicted could reduce CO 2 emissions in the country (Ayu, 2018). Focusing on the distributional impact of a carbon tax, it is estimated that the intervention in Indonesia is not necessarily regressive (Yusuf & Resosudarmo, 2015).…”
Section: Introductionmentioning
confidence: 99%